Safety and feasibility analysis of indocyanine green guided preservation of upper rectal vessels in laparoscopic radical resection of sigmoid cancer - MENG Qingliang; XIE Guangwei; ZHANG Zhengguo; YANG Yong (Zhongguo linchuang yanjiu, 2024)
Objective To investigate the safety and feasibility of indocyanine green guided preservation of the superior rectal artery in patients undergoing laparoscopic radical resection for sigmoid cancer. Methods A total of 73 patients who underwent laparoscopic radical resection of sigmoid cancer in the Department of General Surgery of Xuzhou Central Hospital from October 2019 to February 2024 were analyzed retrospectively. The patients were randomly divided into SRA group (superior rectal artery preservation, n=30) and control group (inferior mesenteric artery high ligation, n=43). The operation time, intraoperative blood loss, incidence of anastomotic fistula and total number of lymph node dissection were compared between the two groups. Results All patients completed the operation successfully and there was no perioperative death. There was no significant difference in operation time, intraoperative blood loss and total number of lymph node dissection between two groups (P＞0.05). The incidence rate of anastomotic fistula in control group was slightly higher than that in SRA group, but the difference was not significant ［14.0%(6/43)  vs 0, χ2=2.899, P=0.089］. Conclusion In laparoscopic radical resection for sigmoid cancer, the application of indocyanine green-guided preservation of SRA while ensuring the clearance of group 253 lymph nodes, compared to traditional high ligation of the inferior mesenteric artery, does not affect the duration of surgery, blood loss, surgical safety, or the number of excised lymph nodes. It plays a certain role in reducing the occurrence of anastomotic fistula.